The Quasi-Sure Limit of Convex Combinations of Nonnegative Measurable Functions. (1st January 2019) - Fan, Yulian
Abstract : This study shows that, for a sequence of nonnegative valued measurable functions, a sequence of convex combinations converges to a nonnegative function in the quasi-sure sense. This can be used to prove some existence results in multiprobabilities models, and an example application in finance is discussed herein.